TINGKAT KESUKAAN KONSUMEN TERHADAP PEWARNA ALAMI DAUN SIRIH (Piper betle L) DAN DAUN MANGGA (Mangifera indica) PADA SERAT KENAF (Hibiscus cannabinus L) - Pratiwi Jati Palupi; syahdiyanor Syahdiyanor; Ali Sadikin (Universitas Nahdlatul Ulama Kalimantan Timur, 2022)
Kenaf fiber is a raw material in diversified products, such as paper, wall coverings, car interiors, geotextiles, soil safer, fiber drain, particle board, and plastic reinforcement as well as raw material for the biofuel industry. Organic kenaf fiber is yellowish white but when it is processed it is light brown and shiny. In improving the appearance to make it more attractive to consumers and high selling power, it is necessary to have a dyeing process for kenaf fiber. The dyes used in kenaf fiber are natural dyes because they are non-toxic, renewable, easily degraded and environmentally friendly. The advantages of using natural dyes are because they have economic value, are environmentally friendly and are easily available in the surrounding environment, such as mango leaves and betel leaves which can produce color pigments, namely mangiferine and anthocyanin pigments. This study aims to determine the effect of kenaf fiber added with natural dyes (mango leaves and betel leaf) on the color, texture, and aroma of kenaf fiber and to determine the level of consumer preference for kenaf fiber with natural dyes. This research was tested using the Hedonic Test method, using a questionnaire with 40 untrained panelists (consumers) with data obtained based on panelist responses using a hedonic scale analyzed by the Kruskal-Wallis test. The results showed that there was no significant effect on kenaf fiber that had been given natural dyes of betel leaf and mango leaf on the color, texture, and aroma of kenaf fiber. However, from the results of the average level of consumer preference, panelists on average tend to like the color and are neutral to the texture and aroma of kenaf fiber with natural dyes of mango and betel leave.